2021
DOI: 10.1111/jfbc.14025
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical potential of mushroom bioactive metabolites and their food functionality

Abstract: Numerous mushroom bioactive metabolites, including polysaccharides, eritadenine, lignin, chitosan, mevinolin, and astrakurkurone have been studied in life‐threatening conditions and diseases such as diabetes, cardiovascular, hypertension, cancer, DNA damage, hypercholesterolemia, and obesity attempting to identify natural therapies. These bioactive metabolites have shown potential as antiviral and immune system strengthener natural agents through diverse cellular and physiological pathways modulation with no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 273 publications
(187 reference statements)
0
5
0
Order By: Relevance
“…However, they might work in different ways, such as balancing inflammatory factors, repairing the intestinal mucosal barrier, improving intestinal microecology, etc . 7 For example, Cordyceps sinensis polysaccharide can stimulate the secretion of cytokines such as TNF-α (tumor necrosis factor-α), IFN-γ (interferon-γ) and IL-17 (interleukin-17) in CTX-induced mucosal immunosuppressed mice, thus alleviating CTX-induced intestinal mucosal immunosuppression. 8 The glucomannan in aloe vera gel can reduce intestinal epithelial cell damage, inulin is commonly reported to be fermented by intestinal microorganisms into large amounts of SCFAs, and fucoidan can alter gut microbiota and mitigate intestinal mucosal injury induced by cyclophosphamide.…”
Section: Introductionmentioning
confidence: 99%
“…However, they might work in different ways, such as balancing inflammatory factors, repairing the intestinal mucosal barrier, improving intestinal microecology, etc . 7 For example, Cordyceps sinensis polysaccharide can stimulate the secretion of cytokines such as TNF-α (tumor necrosis factor-α), IFN-γ (interferon-γ) and IL-17 (interleukin-17) in CTX-induced mucosal immunosuppressed mice, thus alleviating CTX-induced intestinal mucosal immunosuppression. 8 The glucomannan in aloe vera gel can reduce intestinal epithelial cell damage, inulin is commonly reported to be fermented by intestinal microorganisms into large amounts of SCFAs, and fucoidan can alter gut microbiota and mitigate intestinal mucosal injury induced by cyclophosphamide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, considering the beneficial effects, the use of mycoproteins has been reported in a wide variety of food products, including baked goods (such as pasta, breads, and cookies, refs. [ 99 , 100 , 101 , 102 , 103 ]), meat products [ 89 ], and dairy products [ 104 ], as shown in Figure 2 . Beyond the nutritional value, improvements in physicochemical and/or organoleptic characteristics have also been reported.…”
Section: Edible Fungimentioning
confidence: 99%
“…However, except for these two reports, there have been few direct reports on the foaming properties of fungal proteins. Ishara et al found that the FC and FS values of edible fungi were 6.1–131.5% and 3.3–69.6%, respectively, but due to the lack of protein data, the relationship of the proteins with the foam performance in edible mushrooms was not analyzed [ 146 ]. Similarly, using ultrafiltration membrane separation, Longchamp et al obtained by-products with a good foam ability and foam stability from Quorn cell fermentation broth, but it was hard to confirm the effect of the protein because the constitutes in the by-products were too complex [ 147 ].…”
Section: Physicochemical Characteristics Of Animal Alternative Proteinsmentioning
confidence: 99%